Caliciviral protein-based artificial translational activator for mammalian gene circuits with RNA-only delivery - Hideyuki Nakanishi (Nature Portfolio, 2020)
Synthetic RNA-based circuits allow for gene regulation without the risk of mutagenesis. Here the authors demonstrate a Caliciviral VPg-based Translational activator which allows translational activation of synthetic mRNAs.